Lysophosphatidic Acid Induced Apoptosis, DNA Damage, and Oxidative Stress in Spinal Cord Neurons by Upregulating LPA4/LPA6 Receptors - Yifan Yang; Jing Xu; Qingxin Su; Yiran Wu; Qizheng Li; Zongren Ma; Tao Ding (Mediators of Inflammation)
Lysophosphatidic acid (LPA) has disruptive effects on lumbar spinal stenosis (LSS). Recently, LPA has been reported to be involved in spinal cord neuronal injury and toxicity, promoting the pathogenesis of LSS. However, the exact effects of LPA on spinal cord neurons remain unknown. The purpose of this study is to investigate the effects of LPA (18 : 1) on spinal cord neuronal cytotoxicity, apoptosis, DNA damage, and oxidative stress. After clinical detection of LPA secretion, spinal cord neurons were treated with LPA (18 : 1); cell viability was analyzed by MTT assay, and LDH leakage was detected by LDH kit; cell apoptosis was detected by flow cytometry; ROS production was measured by DCFDA staining and MitoSOX Red Staining; the activation of the Gα12/Gα13 signaling pathway was detected by serum response factor response element (SRF-RE) luciferase reporter gene; the relationship among LPA, LPA4/6, and ROCK was examined by western blotting. In spinal cord neurons treated with LPA (18 : 1), cellular activity decreased and LDH release increased. The Rho kinase inhibitor (Y-27632) can attenuate LPA-induced apoptosis, DNA damage, and oxidative stress in spinal cord neurons. Moreover mechanistic investigation indicated that LPA (18 : 1) activates Gα12/13–Rho–ROCK2-induced apoptosis, DNA damage, and oxidative stress in spinal cord neurons by upregulating LPA4/LPA6 receptors. Further, the Rho kinase inhibitor Y-27632 attenuates the effects of LPA by downregulating LPA4/LPA6 receptors. Taken together, the possible mechanism by which LPA secretion in LSS patients aggravates patient injury was further elucidated using an LPA-induced spinal cord neuronal injury cell model in vitro.